Impact Evaluation of The Legal Aid Program fo The Poor Community in Malang Regency, East Java Province - Aji Ramadhan Choirur Rofiansyah; Antun Mardiyanta; Tuan Nooriani Tuan Ismail (Dinasti International Journal of Education Management And Social Science, 2025)
Access to justice is a fundamental principle in a democratic legal system, reflecting the right of every individual to obtain equal legal protection regardless of social or economic background. In Malang Regency, the provision of legal aid for the poor and vulnerable groups is regulated by Malang Regent Regulation No. 31 of 2023, which aims to ensure that these rights are respected. However, challenges in implementation remain, including the absence of empirical evaluation regarding the program’s impact on local communities. This study adopts a qualitative approach with an interpretivist epistemological stance to evaluate the impact of the legal aid program in Malang Regency. Through in-depth interviews and contextual analysis, the research explores community experiences in accessing legal services and the socio-cultural challenges that influence them. Findings indicate that limited access to information, education, resources, and legal assistance hinders the empowerment of vulnerable groups in realizing their fundamental rights. The study emphasizes the importance of expanding the criteria for legal aid beneficiaries beyond economic factors to include other vulnerable groups, such as persons with disabilities, women and children survivors of violence, and street children. Using the theoretical frameworks of Public Policy Analysis and Program Evaluation, this study argues that effective legal aid provision requires not only procedural mechanisms but also community-based empowerment strategies and the integration of local cultural values. Policy recommendations include strengthening the institutional capacity of legal aid organizations, expanding public legal education, increasing budget allocations, and fostering collaboration between government agencies, community leaders, the private sector, and universities. This study contributes to public policy discourse by asserting the need for inclusive and socially just access to legal protection.